A Blockchain-Based Approach for Privacy Control of Patient’s Medical Records in the Fog Layer - Silva, Cícero A. da; Aquino Júnior, Gibeon S. de; Melo, Sávio R. M. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2019: Proceedings of the 25th Brazilian Symposium on Multimedia and the Web, 2019)
The Fog Computing paradigm is characterized by providing Cloud capabilities closer to applications and data sources. Thus, it has been widely used as an approach to avoid delays in accessing patients’ medical information. However, the privacy of patient’ data is a critical requirement in this environment because they contain intimate information from each person. This paper presents a new approach that uses Blockchain to ensure the privacy of patient medical data in this Fog Computing environment. We describe the design of this approach and present an implementation of it, which demonstrates the privacy control process exercised by the patient. Finally, we discuss the security and privacy aspects provided by our approach.